Analisis Pengembangan Kewirausahaan Melalui Destinasi Wisata: Studi Pada Santera De Laponte Kota Batu Malang - Nuranisah, Siti; Nurfadila, Dian; Ardaneshwari, Yulita Septi; Purwanto, I Gede Aditya; Maharani, Keysha Putri; Rachmad (JPS: Journal of Publicness Studies, 2025)
The development of tourism destinations plays a vital role in fostering entrepreneurship and strengthening the local economy. This study aims to examine the role of the Santerra De Laponte tourism destination in Batu City in creating entrepreneurial opportunities, identify factors  influencing  tourism-based  entrepreneurship  development, and analyze management strategies in empowering local businesses. Employing a qualitative method with a descriptive approach through direct field observations, the results demonstrate that Santerra De Laponte has fostered the growth of various local enterprises such as culinary, souvenirs, photography services, costume rentals, and tourist transportation contributing to increased community income. The success of this entrepreneurial development is underpinned by innovative attractions, strategic location, excellent accessibility, and collaboration between management and the community. This study concludes that effective tourism destination management can serve as a sustainable catalyst for local entrepreneurship.